The Criminalization of Trading in Influence in Lithuania - Mickevičiūtė, Laura (Teisė, 2018)
The aim of this article is to reveal the development of the criminalization of trading in influence. This articlereveals the origins, limits and amendments of the criminalization of trading in influence according to criminal laws,which were in force in various periods in Lithuania.
Keywords: none